EVALUASI KEBIJAKAN PEMUNGUTAN DAN PENGHITUNGAN SUARA DI TPS DALAM PEMILU 2019 DI KABUPATEN PASANG KAYU - Alamsyah; Irwan Waris; Asrifai (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The aim of the research is to evaluate voting and counting policies at polling stations in the 2019 elections in Pasangkayu Regency, in terms of the registration and administration of DPK voters. Evaluation of Voting and Vote Counting Policies, using 4 Aspects according to Bardach in Patton & Sawicki (1986: 156–167): namely the Technical Feasibility Aspect of the policy, namely that there needs to be regulation of the time for checking voters, before voting, and providing Offline DPT. Aspects of economic and financial support that assess how much money is needed for the technical implementation of policies, that there is a need to increase and increase the budget for technical guidance, simulation and honorarium for ad hoc agencies. In terms of political support, it is necessary to be more intense in building a sustainable understanding of cooperation in order to make the election a success. As well as aspects of implementing organizational support, there needs to be internal strengthening through coordination meetings, monitoring and evaluation as well as increasing technical capacity for all KPPS with technical guidance and simulations. This type of research is descriptive research, namely providing an overview and explanation of the subject being studied. The research results show that the voting and counting of votes at the TPS in the 2019 elections in Pasangkayu Regency, in terms of the registration and administration of DPK voters, was not carried out well, due to the lack of support for online DPT checking and limited checking time, as well as the understanding of KPPS officers regarding their duties and functions. needs to be improved.